Patients’ Perspectives on the Experience of Absconding from a psychiatric hospital: a qualitative study - Kaggwa, Mark Mohan; Acai, Anita; Rukundo, Godfrey Zari; Harms, Sheila; Ashaba, Scholastic (BMC psychiatry, 2021)
Absconding (i.e., escaping) is common among patients with mental illness admitted to psychiatric hospitals. Patients use various strategies to make absconding successful due to the experiences faced during admission. We conducted a study to identify patients’ perspectives on the experience of absconding from the psychiatry facility.We conducted 10 in-depth interviews with patients with a history of absconding from the hospital who were accessing care at the Mbarara Regional Referral Hospital in Mbarara city Uganda. Interviews were audio-recorded, translated when required, transcribed into English, and analyzed thematically to identify relevant themes.Participants ranged in age from 18 to 55 and the majority (n = 9) were male. Most had absconded at least twice from a psychiatric facility. We identified different experiences that influenced patients’ engagement in absconding from the psychiatry hospital ward. These included: (1) stigma, (2) experiences with caregivers: mixed emotions, (3) poor resources and services, and (4) the influence of mental illness symptoms. The loneliness of stigma, negative emotions associated with the loss of important roles given the nature and framework of caregiving on the psychiatric ward, as well as the stress of limited resources were a salient part of the patient experience as it relates to absconding.Our findings indicate that absconding is a symptom of a larger problem with a mental health system that perpetuates stigma in its design, isolates patients and makes them feel lonely, and forces patients to rely on caregivers who infantilize them and take away all their freedom in a facility with no basic services. For many patients, this makes absconding the only option. Within such a system, all stakeholders (policymakers, health-care providers, caregivers, and patients) should be involved in rethinking how psychiatric facilities should be operated to make the journey of patient recovery more positive.
Keywords: Mental illness, Psychiatric hospitals, Stigma, Caregivers, Absconding, Infantilization, Loneliness, Mental health system, Uganda, Escape